Photodynamic therapy of hepatocellular carcinoma using tetra- triethyleneoxysulfonyl zinc phthalocyanine as photosensitizer - Ogbodu, Racheal O.; Nitzsche, Bianca; Ma, Andi; Atilla, Devrim; Guerek, Ayse Gul; Hoepfner, Michael (Elsevier Science Sa, 2020)
The palliative treatment options for advanced hepatocellular carcinoma (HCC) are currently not satisfying. The use of photodynamic therapy (PDT) has gained much attention in the treatment of several cancers and has been approved as an alternative approach in treating different forms of cancers. We investigated for the first time the PDT effects of tetra-triethyleneoxysulfonyl zinc phthalocyanine (ZnPc) on HCC cells. Photoactivation of ZnPc loaded HCC cells resulted in a dose- and time- dependent growth inhibitory effect, the production of reactive oxygen species (ROS), induced cytotoxic effects and the induction of apoptosis in the investigated HCC cells (HepG2 and Huh-7). ZnPc-PDT inhibited the proliferation of HCC cells by up to 90% accompanied by a downregulation of the activity and expression of the proliferation relevant mitogen-activated protein kinase (MAPK)-protein extracellular signal-regulated (ERK 1/2). Moreover, an up-regulation of proapoptotic BAX and a downregulation of antiapoptotic B-cell lymphoma 2 (Bcl-2) expressions were observed with both proteins implicated in mitochondria-driven apoptosis. The investigation of the anti-tumor effect of ZnPc-PDT in vivo using the chicken chorioallantoic membrane assays (CAM) revealed a strong reduction in the size of HCC tumor plagues > 80% after 4 days of PDT-treatment without affecting the survival of the developing embryo. The pronounced anti-proliferative and anti-tumor effects of ZnPc-PDT both in vitro and in vivo render ZnPc-PDT as a promising palliative treatment option for hepatocellular carcinoma.
Keywords: Hepatocellular carcinoma; Photodynamic therapy; Phototoxicity; Apoptosis; Chorioallantoic membrane assays